Age at Sexual Debut and Reproductive Health Behaviour of Adolescents in Ga Mashie in Ghana. - Yeboah, E.O. (University of Ghana, 2014)
The objective of the study was to examine the relationship between age at first sex and reproductive health behaviour among adolescents with specific emphasis on multiple sexual partnerships and the implication for public policy. The study employed data from the Edulink Data: Urban Health and Poverty Survey –Wave II which was conducted under the auspices of the Regional Institute of Population Studies, University of Ghana in the year 2011. Age at first sexual intercourse is the independent variable, whereas the socio-economic characteristics of respondents were the control variables. These were age, sex, marital status, occupation, religion, locality, ethnicity, income and education. Both bivariate and logistic regression analyses were employed to identify the most important factors determining sexual partnerships. Binary regression model was used for the multivariate analysis. The study revealed that about 52% of adolescent aged 15 to 18 years are engaging in multiple sexual partnerships in urban poor communities in Accra. This sexual behaviour varies with socio-economic status of respondents. The study further indicates that the most influencing factors are early age at first sex, religion, sex and marital status. For example, the bivariate analysis indicated that age at first sex has an inverse relationship with multiple sexual partnerships, with almost 65% multiple sexual partners for adolescent who had their first sex before age 15. It was also realized that adolescent within the age group 20 to 24 are more likely to have multiple sexual partners than those aged 15-19 years. Secondly, adolescent with middle/JHS education are as likely to have multiple partners. The study made several recommendations including the importance of making sex education as part of the school curricular from basic to Senior High School and the setting up of recreational and community centers across urban poor communities. At the community centers, indoor and outdoor games as well as counselling sections on issues about sex and the importance of family planning should form part of the programs for the youth.
Keywords: Sexual; Reproductive; Health; Behaviour; Adolescent; Ga Mashie